Pola Komunikasi Keluarga dalam Pembentukan Kepribadian Anak - Yulianti, Yulianti; Utami, Sri; Febriani, Widia (Indonesian Journal of Educational Counseling, 2023)
The research conducted in this literature review utilized a documentation study approach, analyzing ten theoretical studies sourced from articles. The research focused on "family communication patterns" and "child personality." The findings strongly support the notion that effective communication within the family is vital for the healthy growth and development of children's personalities. When communication patterns are well-established, it fosters open and honest relationships between parents and children, allowing parents to understand better and cater to their children's needs.